The Relationship Between Vision And Ability To Activity In Post Cataract Surgery Patients At Pandega Hospital, Pangandaran District - Ganjar Nugraha; Siti Rohimah; Nina Rosdiana (Asy-Syifa : Journal of Science and Technology Nursing, 2023)
Purpose: This study aims to determine the relationship between loneliness and nomophobia among S1 nursing students at STIKes Muhammadiyah Ciamis. Methods: The method used in this research is quantitative research with a correlational approach. The population in this study was 132 undergraduate nursing students at STIKes Muhammadiyah Ciamis. Sampling is done using the G*Power application. The number of samples in this study was 42. The research was conducted on March 28–29, 2023. Results: The results showed that the picture of loneliness in students mostly experienced moderate loneliness, as many as 20 respondents (47.6%). The picture of nomophobia students mostly experienced moderate nomophobia; as many as 17 respondents (40.5%) The results of the data analysis show a p-value of 0.692 > 0.05. Conclusions: This study concludes that there is no relationship between loneliness and nomophobia among S1 nursing students at STIKes Muhammadiyah Ciamis.